Lipidomic profiling reveals phenotypic diversity and nutritional benefits in Ficus carica L. (Fig.) seed cultivars - Irchad, Ahmed; Ouaabou, Rachida; Aboutayeb, Rachid; Razouk, Rachid; Houmanat, Karim; Hssaini, Lahcen (Frontiers in Plant Science, 2023)
Introduction Ficus carica L. seeds are a substantial source of minor oil with high unsaturation levels and potent antioxidant properties. The study aims to evaluate the mineral composition, lipodomic profile, and vibrational fingerprints of 22 fig genotypes utilizing FTIR-ATR techniques and chemometrics. Methods FTIR-ATR spectroscopy and chemometric techniques were employed to examine the phenotypic diversity of fig seeds. The investigation was performed in detail. The research analyzed twenty-two fig genotypes to assess their nutritional properties, genetic relationships, and potential applications. Results The results demonstrate substantial nutritional benefits related to fig seeds, which could serve as genetic resources for selection programs for extracting vegetable oil and functional ingredients. Additionally, a detailed lipodomic profile analysis led to the categorization of the genotypes into four unique clusters. The study uncovered new insights regarding the nutritional composition of the samples, while also highlighting significant similarities and differences. The findings showcased the phenotypic diversity within the studied fig germplasm, which is likely attributed to underlying genetic factors. These accessions offer a valuable gene pool for future breeding programs and diverse applications involving fig seeds. Discussion This work contributes to the selection of potential genotypes for scientific and industrial purposes. Furthermore, the application of FTIR and chemometrics revealed a noteworthy diversity of patterns, emphasizing the previously underestimated significance of this aspect in evaluating the chemodiversity of the species.